Reconfiguring Indonesia’s Labor Law Framework to Address Protection Gaps in the Gig Economy Era Following the Constitutional Court’s Decision - Agusmidah; Shalihah, Fithriatus; Aka, M Virsa (Jurnal IUS Kajian Hukum dan Keadilan, 2026)
The Indonesian labor market is shifting toward greater flexibility, driven by a surge in layoffs in the post-Covid-19 period (2020-2024), limited employment opportunities in the manufacturing sector, the demographic bonus, and the rapid expansion of platform-based industries and digital commerce. This shift has contributed to the rise of the gig economy, which has yet to provide adequate job security and decent working conditions. This paper examines the growing employment uncertainty within the gig economy and discusses how the government can respond through fairer and more responsive regulations to support a decent standard of living and sustainable worker welfare. This study employs a normative legal research method with legislative and conceptual approaches, relying on secondary data in the form of primary materials and scholarly literature from reputable academic sources. The findings indicate the need to revise labor laws, as mandated by Constitutional Court Decision No. 168/PUU-XXI/2023, which calls for the prompt enactment of a new Labor Law capable of providing holistic protection. Lessons from several developed countries highlight the need for regulatory synchronization both vertically, between laws and their implementing regulations, and horizontally, between the Manpower Law and other related policies. Labor regulations should cover both formal and informal workers through a work-life balance approach for all, with the aim of promoting fairness, welfare, and sustainable decent work. Thus, the framework of labour protection needs to be recalibrated to include gig workers.